2001
DOI: 10.1007/bf03190373
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of melatonin with the liver microsomal cytochrome P450 system of rats and humans in vitro and effects on the P450 system and the antioxidative status in rat liver after acute treatment

Abstract: In vitro melatonin binds to human and rat liver microsomal cytochrome P-450 (P450) according to a type II substrate. The affinity is similar to that of aniline with a general left-shift. Melatonin interferes with model monooxygenase reactions indicative of different P450 forms in humans and rats (in humans according to the lower specific P450 content less pronounced): the strongest inhibition was found for ethoxyresorufin O-deethylation, indicating the binding to P450 1A, the binding to P450 2B (ethoxycoumarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…On the other hand, 6‐hydroxylation of melatonin is mediated by CYP1A1, CYP1A2 and CYP1B1 but not CYP2E1 and CYP2A6 [29]. In vitro study showed that melatonin strongly binds to CYP1A, and distinctly less to CYP2B or CYP3A [30]. We have already demonstrated that S ‐allylmercaptocysteine (SAMC), an organosulfur compound in aged garlic extract, inhibits CYP2E1 activities, resulting in reduced generation of NAPQI and suppression of GSH depletion [11].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, 6‐hydroxylation of melatonin is mediated by CYP1A1, CYP1A2 and CYP1B1 but not CYP2E1 and CYP2A6 [29]. In vitro study showed that melatonin strongly binds to CYP1A, and distinctly less to CYP2B or CYP3A [30]. We have already demonstrated that S ‐allylmercaptocysteine (SAMC), an organosulfur compound in aged garlic extract, inhibits CYP2E1 activities, resulting in reduced generation of NAPQI and suppression of GSH depletion [11].…”
Section: Discussionmentioning
confidence: 99%